IMPROVING STUDENTS’ READING COMPREHENSION THROUGH QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY - Yahya Muhaimin; Sitti Nurjannah; Muhammad Taufik (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The purpose of this research is to find out and investigate whether the use of the Question-Answer Relationship (QAR) Strategy improves the reading comprehension of students in class X at SMA Cendrawasih Makassar. This research is quantitative research with research methods using quasi experiments, the research design used is pre-test and post-test using experimental classes and control classes. The data collection technique used was a multiple-choice test with 40 questions and 10 essay questions which were declared valid. The sample for this research was class X, totaling 30 students selected using the purposive sampling method and divided into two classes. 15 students as an experimental class who were taught using QAR Strategy and 15 students as a control class who did not use QAR Strategy. The data analysis technique used was the normality test, homogeneity test, and hypothesis testing using the independent sample t-test. The research results show that the Question Answer Relationship (QAR) strategy is effective in improving students' reading comprehension. This can be proven by an increase in the average pre-test score of 43.00 and the average post-test score of 90.00. After checking the hypothesis, the results show t-obtained 5.622 which is higher than the t-table critical value of 1.76. It can be concluded that (Ho) is rejected and (Ha) is accepted. This means that there is a significant difference before and after using the Question Answer Relationship (QAR) strategy and applying the Question-Answer Relationship (QAR) strategy to improve students' reading comprehension abilities. Moreover, students gave positive responses to the use of this strategy.